1999
DOI: 10.1007/s004649900956
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic treatment vs open surgery in the solution of major incisional and abdominal wall hernias with mesh

Abstract: Laparoscopic treatment of postoperative eventration and primary ventral hernia reduces complications and relapse rates, eliminates reintervention through mesh infection, reduces operative time, and considerably shortens the hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
235
2
19

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(261 citation statements)
references
References 6 publications
5
235
2
19
Order By: Relevance
“…Arroyo et al 2 in their retrospective study showed that using meshes for paraumbilical hernia repair, the recurrence rate could be reduced to 0.95%. In this retrospective study, the recurrence rate was 8 However, some risk factors could influence the paraumbilical hernia recurrence. Many retrospective studies have analyzed and assessed independent risk factors for paraumbilical hernia recurrence.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Arroyo et al 2 in their retrospective study showed that using meshes for paraumbilical hernia repair, the recurrence rate could be reduced to 0.95%. In this retrospective study, the recurrence rate was 8 However, some risk factors could influence the paraumbilical hernia recurrence. Many retrospective studies have analyzed and assessed independent risk factors for paraumbilical hernia recurrence.…”
Section: Discussionmentioning
confidence: 75%
“…The first operative techniques included simple suture herniorrhaphy, Mayo or keel repair techniques. The suture repair techniques increased the recurrence rate up to 19 to 54.0% 3,[6][7][8] . The use of prosthetic materials reduces the recurrence rate to 15.0 to 20.0% 6 .…”
Section: Discussionmentioning
confidence: 99%
“…19 In the underlying trial, the use of mesh was mandatory for all incisional hernia repairs, frequently using polypropyl-ene material in the sublay or intraperitoneal position. Shorter operative time for laparoscopic incisional hernia repair was reported by a number of recently published studies, 13,14,20,21 while other studies show no differences or longer operative times in the laparoscopic group. 22,23 In small incisional hernia, introduction of trocars and positioning of instruments can be time-consuming.…”
Section: Figure-2mentioning
confidence: 82%
“…1. All patients included in the study underwent ultrasound evaluation of the abdominal wall with high-frequency linear probe (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and if necessary also with convex probe (in 20 cases; equal to 21.5 %).…”
Section: Methodsmentioning
confidence: 99%
“…The gradual diffusion of the laparoscopic approach is justified by the fact that they respected the principles of tension-free repair and by the results obtained are promising, and, as reported in several series of statistical studies, often higher than those of traditional techniques (in particular, less post-operative pain, fewer respiratory complications, rapid mobilization of patient with fewer thromboembolic complications; reduction un the time of hospitalization, the rate of surgical site infection and recurrence; best esthetic result) [3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%